Exposing the Unfinished Business of Building Public Administration in Late Democracies: Lessons from the COVID‐19 Response in Brazil. (24th August 2021) - Puppim de Oliveira, Jose A.; Berman, Evan M.
Abstract: The COVID‐19 pandemic has exposed fundamental flaws in the design of public administration in late democracies. While much writing to date focuses on the initial and vital responses to COVID‐19, the magnitude of this event also furthers insights into the risks of incomplete institutional designs and practices, such as the case of Brazil, an example of the administrative flaws in late democracies. This article is not a critique of responses to COVID‐19 per se, but an examination of these considering democratization processes that include state‐building and the need for another push in administrative and political reforms. Shortcomings in state‐building, which existed before COVID‐19, inflict heavy costs on society and, if left unaddressed, add to the costs of future disasters and unraveling of support for state and democratic institutions.